The Prospects of Intellectual Property Rights as a Credit Collateral: An Indonesia-Singapore Comparative Study - Rifqi, Muhammad; Roisah, Kholis; Lestari, Sartika Nanda (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: The development of the creative industry has an impact on the need for capital. The government has made new policies related to the financing mechanism of the creative economy through Peraturan Pemerintah (PP) Number 24 of 2022 concerning the Implementation of Law Number 24 of 2019 concerning the Creative Economy. The government is trying to provide support in the form of a credit financing scheme with IPR as a collateral to financial institutions.Purpose/Objective Study: This study aims to determine the prospects of IPR as a credit guarantee after the issuance of PP Number 24 of 2022. To see the extent of the effectiveness of the PP, this study presents a comparison of IPR commercialization in Singapore, which is one of the countries that has successfully implemented IPR as a credit.Design/Methodology/Approach: The research method used is normative juridical with analytical descriptive specifications.Findings: The results indicated that to implement IPR as a credit guarantee, collaboration between institutions is needed, and several instruments must be fulfilled, namely concerning legal regulations, government institutions, financial institutions, valuation institutions, insurance institutions, and secondary markets. Indonesia does not fully have these six instruments, especially in terms of institutions related to valuation institutions and their technical implementation guidelines, insurance institutions in case of bad credit, and the secondary market as the last place to sell IPR assets. The implication is that IPR-based credit financing for creative economy actors in Indonesia has not run optimally.Paper Type: Research Article